2009
DOI: 10.1116/1.3253612
|View full text |Cite
|
Sign up to set email alerts
|

Defectivity issues in topcoatless photoresists

Abstract: One method currently being employed to reduce the overall lithography process complexity and cost is the utilization of a topcoatless photoresist. The development of these materials administers an additive to create the same hydrophobic characteristics as those created by advanced topcoats. The main challenge for topcoatless resists is to increase the hydrophobicity without causing too much inhibition at the resist surface which leads to bridging or residue-type defects. The key to such a design lies in creati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Unlike other methods to fabricate SAM‐based devices (of the sort shown in Figure ), our technique is compatible with template‐stripped bottom‐electrodes and does not require patterning of the bottom‐electrode. This ensures that the electrodes supporting the SAMs are clean and never had been exposed to photoresist (which is often difficult to remove completely) and only briefly exposed to the ambient (few seconds), and do not contain edges at which SAMs cannot pack well . The stabilization of the top‐electrode minimizes the user‐to‐user variation in contacting the SAMs, defines the geometrical area of the junctions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike other methods to fabricate SAM‐based devices (of the sort shown in Figure ), our technique is compatible with template‐stripped bottom‐electrodes and does not require patterning of the bottom‐electrode. This ensures that the electrodes supporting the SAMs are clean and never had been exposed to photoresist (which is often difficult to remove completely) and only briefly exposed to the ambient (few seconds), and do not contain edges at which SAMs cannot pack well . The stabilization of the top‐electrode minimizes the user‐to‐user variation in contacting the SAMs, defines the geometrical area of the junctions.…”
Section: Discussionmentioning
confidence: 99%
“…i) The bottom‐electrode needs to be patterned which normally requires lithography. Patterning by e‐beam‐ or photolithography often leaves resist residues on the electrode behind that are difficult to remove completely and consequently result in defective SAMs . ii) The bottom‐electrodes contain exposed edges at which SAMs cannot form densely packed layers .…”
Section: Introductionmentioning
confidence: 99%
“…Contact between PR and water in general does not cause watermark defects, as it is common to pre-rinse or post-rinse wafers before or after certain process steps. [41][42][43] showed that no watermark defects occur, if droplets are removed by airjet blowing before complete evaporation, which indicates that the terminal phase of the evaporation process is the detrimental one. 44 Near complete evaporation, any dissolved components that have been leached from the photoresist [15][16][17]19,45,46 during the lifetime of the droplet are strongly enriched in concentration.…”
Section: Relevance To Technological Applicationsmentioning
confidence: 99%
“…With the increase of circuit density and decrease in feature size in recent years, photolithography process induced defects have shown adverse effect on device yield, quality and performance. [1][2][3][4][5][6][7] During the photo resist development, a range of different types of defects could occur, such as missing of contacts, pattern collapse, residue formation, no development and crown defects. [2][3][4]8) Specifically, the crown defect is located in the exposed area of the gate pattern and unexposed area of the implant and hole patterns.…”
Section: Introductionmentioning
confidence: 99%